2019
DOI: 10.1038/s41560-019-0456-5
|View full text |Cite|
|
Sign up to set email alerts
|

Current understanding and challenges of solar-driven hydrogen generation using polymeric photocatalysts

Abstract: The use of hydrogen as a fuel, when generated from water using semiconductor photocatalysts and driven by sunlight, is a sustainable alternative to fossil fuels. Polymeric photocatalysts are based on earth-abundant elements and have the advantage over their inorganic counterparts that their electronic properties are easily tuneable through molecular engineering. Polymeric photocatalysts have developed rapidly over the last decade, resulting in the discovery of many active materials. However, our understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
588
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 752 publications
(630 citation statements)
references
References 155 publications
6
588
1
1
Order By: Relevance
“…Conductive polymers are very interesting organic macromolecules, widely considered for the design of advanced hybrid materials with photocatalytic properties [276], thanks to their good processability, especially through solution processes [277]. Conductive polymers can provide matched band structures with other inorganic semiconductors, such as metal oxides nanostructures, reducing the recombination of photogenerated electron-hole pairs for obtained hybrid composite photocatalysts [278,279].…”
Section: Conductive Polymers-based Hybrid Nanomaterialsmentioning
confidence: 99%
“…Conductive polymers are very interesting organic macromolecules, widely considered for the design of advanced hybrid materials with photocatalytic properties [276], thanks to their good processability, especially through solution processes [277]. Conductive polymers can provide matched band structures with other inorganic semiconductors, such as metal oxides nanostructures, reducing the recombination of photogenerated electron-hole pairs for obtained hybrid composite photocatalysts [278,279].…”
Section: Conductive Polymers-based Hybrid Nanomaterialsmentioning
confidence: 99%
“…Thus, photocatalytic water splitting into hydrogen has been recognized as the "Holy Grail" of the renewable energy research. Up to now, various impressive photocatalyst materials have been developed for efficient and stable photocatalytic hydrogen production [134][135][136][137][138][139]. However, most of the employed photocatalysts are still .…”
Section: Hydrogen Generationmentioning
confidence: 99%
“…Distinct from their inorganic counterparts,organic photocatalysts are potential "600 nm-class photocatalyst" for solar fuel production. [3] There are practical reasons for stressing on the 600 nm-class photocatalysts.Except for solar driven PV-electrolysis,a ttaining at argeted 10 %S TH (solarto-hydrogen) efficiency is challenging with current set of inorganic photocatalysts that work below 600 nm. Contrarily, it was theoretically demonstrated that at andem structure of light-absorbing materials with band gaps in the range of 1.6-1.8 eV would have practical implication in achieving aS TH efficiency at > 25 %w hen optimum device design related requirements are full-filled.…”
Section: Introduction:r Ise Of Polymeric Photocatalysts For Hydrogen mentioning
confidence: 99%
“…[11] Ah istorical development of polymeric photocatalysts is shown in Figure 2where the field also contains alternative classifications such as compactified polymers (e.g.Pdots) or collapsed MOFs.Interested readers are suggested to read the recently published articles cited in ref. [3] for ac omprehensive overview of the synthesis,p hysicochemical attributes and applications of organic photocatalysts.…”
Section: Introduction:r Ise Of Polymeric Photocatalysts For Hydrogen mentioning
confidence: 99%